2016
DOI: 10.1080/09638288.2016.1236154
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility of medical and psychosocial services following disasters and other traumatic events: experiences of Deaf and hard-of-hearing individuals in Denmark

Abstract: This study has identified significant gaps in post-disaster service provision for D/HH individuals. Results can inform policy makers and other authorities in the position to enhance existing services and/or develop new services for this vulnerable target population. Implications for Rehabilitation Being Deaf or hard-of-hearing compromises a person's ability to obtain and share vital information during times of disaster. Medical and psychosocial services are expected to play critical response roles in times of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Generally, operators and practitioners tend to rely on the relatives of people with disabilities to disseminate specific information. 5 Additionally, natural disasters lead to a state of poverty. Hence, people with disabilities, regardless of their health status and caregiver assistance, need free access to prolonged tailored services.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, operators and practitioners tend to rely on the relatives of people with disabilities to disseminate specific information. 5 Additionally, natural disasters lead to a state of poverty. Hence, people with disabilities, regardless of their health status and caregiver assistance, need free access to prolonged tailored services.…”
Section: Introductionmentioning
confidence: 99%
“…Given that most Deaf clients who enter behavioural health treatment have trauma histories and at least 74% of Deaf individuals in SUD treatment have experienced abuse (Titus et al, 2008), implementing integrated trauma/SUD interventions for this population is a logical first step to address Deaf behavioural health disparities in the United States. However, currently available evidence-based psychotherapies were designed for hearing populations and therefore fail to meet the unique linguistic, developmental, and cultural needs of Deaf clients (Anderson et al, 2017b;Estrada & Beyebach, 2007;Fellinger & Fellinger, 2014;Glickman & Pollard, 2013;Kuenburg et al, 2016;Skot et al, 2017). Most combine traditional talk therapy with client workbooks or handouts, which often contain sophisticated strategies for tracking mood, behaviour, and thoughts, and use psychological jargon throughout.…”
Section: Best Practices In Deaf Mental Healthmentioning
confidence: 99%
“…The lack of universal design and accessibility are not the only factors that increase the disaster risk for persons with disabilities; cultural attitudes, stigma and barriers to their full participation in society have the same impact. This was shown in a UN survey conducted in 126 countries, which found that only 14 per cent of people with disabilities had been consulted about disaster risk management in their communities, implying that their risk reduction needs have been ignored (United Nations Office for Disaster Risk Reduction, 2013; Hunt et al, 2015;Nunnerley et al, 2015;Stough and Kang, 2015;Skøt et al, 2016). This is particularly worrying given that, as a result of climate change, the number of disasters is expected to increase over the next few years (United Nations Refugee Agency, 2017), and therefore the disaster needs of older people and persons with disabilities should be urgently addressed.…”
Section: Introductionmentioning
confidence: 99%